Enhancing French Proficiency With Equitable and Personalized Assessments - Li, Miao; Soni, Shweta; Joseph, Sarah; Ahodetor, Xavier (Imagining SoTL, 2026)
This study examines the impact of three complementary assessment strategies on French language proficiency: standardized evaluation based on the Diplôme d'Études en Langue Française (DELF), personalized verbal feedback, and structured self-reflection. These methods were designed to foster equitable, inclusive, and accessible learning experiences while leveraging research on spaced repetition and retrieval-based learning to strengthen retention and mastery. The project supported diverse learner profiles and prepared students for advanced-level French coursework, targeting competencies in reception, production, interaction, and mediation. Findings indicate that DELF principles—criteria aligned with the Common European Framework of Reference for Languages, authentic communicative tasks, and transparent rubrics—can be adapted beyond formal testing to enrich daily instruction and promote fairness. Personalized verbal feedback enhances learner motivation and engagement. Structured self-reflection tools foster metacognitive awareness and autonomy. These methods were embedded within an instructional model integrating authentic tests, inquiry-based individualized feedback, and backward design principles within self-paced online modules via the Desire2Learn (D2L) platform. Although focused on language education, these strategies demonstrate strong potential for broader contexts, reframing assessment as a dynamic, learner-driven process that promotes continuous development rather than serving solely as a summative measure.